FI’IL MUDHORI’ MANSHUB DALAM BUKU “RIYADHUS SHALIHIN” JILID 1 (Universitas Negeri Semarang, 2012)
The term comes from the Greek Syntax, the sun which means 'with' and tattein which means 'place'. Etymologically, syntax means putting together words into a group of words or sentences. The ficil Mudhori 'could manshub as amyl nashob conceded. Amil nashob there is أن 10, لن, إذن, كي, لام كي, لام الجحود, حتى, فاء السببية, واو معية, and أو. The design of this research study or library research is often referred to as the research literature. Data analysis includes descriptive inductive analysis techniques. The results showed that the factors that led to ficil Mudhori 'be manshub in the book